Belonging to the university or being in the world: From belonging to relational being - Graham, Cameron; Moir, Zack (Journal of University Teaching and Learning Practice, 2022)
In a world characterised by supercomplexity, in which higher education (HE) is in the grip of neoliberal market forces (Barnett, 2000), it is incumbent upon participants in this sector to ask; what does it mean to belong, and to what? ‘Belonging’ has become a buzzword used by institutions to seemingly demonstrate how they seek to include students and help them ‘fit in’ to specific cultures and contexts of learning. A sense of ‘belonging’ may be important for some students at an emotional level; however, in the context of the neoliberal university, we argue that focussing on this concept may have the effect of encouraging students to assimilate to the dominant culture. More subtly, it could be noted that this is part of an ongoing process of inculcating students to the beliefs, values and normative behaviours associated with neoliberalism, arguably reproducing and exacerbating many of the social challenges threatening education, democracy, ecosystems and ultimately our ability to survive on this planet. This theoretical paper challenges the notion of belonging, problematising it as a neoliberal construct of 21st century HE that insidiously invokes a particular notion of ‘community’ which functions to prioritise domestication and conformity to social and economic expectations of a higher education driven by an agenda of employability, entrepreneurialism, and acquisitive individualism. We propose a more meaningful conception of ‘belonging’; based on engaging students in changing their world so as they may belong in the world authentically. We contend that belonging holds greater promise as a means of self-actualisation, liberation, and a way to develop authentic ‘critical being’ (Barnett, 1997) whereby students develop belonging and are not “…subject to the world but able to act autonomously and purposively within it” (ibid. p.4).